320 ERROR AND ADVERSE EVENTS REPORTING: AN ANALYSIS OF 266, 224 REPORTS COMPARING PHYSICIAN AND NURSE TRENDS. Issue 1 (1st January 2007) - Rowin, E.; Lucier, D.; Pauker, S.; Kumar, S.; Chen, J.; Salem, D. N.
Abstract : Objective: To improve of the delivery, effectiveness, and safety of the health care system, clinicians must report adverse events. Improved reporting requires an understanding of current reporting practices concerning medical errors, near misses, and adverse events. This study compared the reporting practices of physicians and nurses. Design: Descriptive study of reported events using a secure, standardized, Web-based reporting system. SETTING: 29 acute care nonfederal U.S. hospitals and one long term care facility that implemented an electronic error reporting system, available to all employees, between August 2000 and December 2005. Methods: Events were classified by impact level on the patient using a standard classification scheme. Both ANOVA and chi-square testing were performed to analyze the significance. Results: 266, 224 events were reported over 7.3 million inpatient-days or 1 event per 27.5 days. Physicians reported 1.1%, nurses 45.3%, and other hospital employees 53.6% of total events. There was no significant difference between academic and nonacademic settings. In academic hospitals, physicians-in-training had a lower reporting rate than did attending physicians ( p < .05). Conclusions: Physicians report fewer and a narrower spectrum of events than nurses; physician reporting rates increase as the impact of the event on the patient increases but decrease for fatal events; nurse rates remain stable across impact levels. Differences exist between how nurses and physicians report events, and it is necessary to understand the underlying reasons behind these variations.